Subjective norms and entrepreneurial intention: Entrepreneurial education as a mediator - Mat Nawi, Farahiyah Akmal; Baistaman, Julaina; Wan Mustapha, Wan Masnieza; Abu Bakar, Hatinah (International Journal of Accounting, Finance and Business, 2025)
Entrepreneurial intention has been widely recognized as a critical predictor of actual entrepreneurial behavior. However, the mechanisms through which subjective norms influence entrepreneurial intention remain less understood, particularly the role of entrepreneurial education. This study aims to examine the mediating effect of entrepreneurial education on the relationship between subjective norms and entrepreneurial intention among Universiti Teknologi MARA (UiTM) students. Using a quantitative approach, data were collected through a structured questionnaire distributed to undergraduate students enrolled in entrepreneurship programs. Structural equation modelling (SEM) was employed to test the hypothesized relationships. The findings reveal that subjective norms have a significant direct effect on entrepreneurial intention, while entrepreneurial education significantly mediates this relationship. The results highlight the importance of designing entrepreneurship education programs that leverage social support to strengthen entrepreneurial intentions. Universities and policymakers are encouraged to integrate social influence elements into entrepreneurial education to better nurture the next generation of entrepreneurs.